THE LIFE OF CONTEMPLATION AND THE LIFE OF ACTION: PLATINUS AND ΦΡΌΝΗΣΙΣ (Годишен зборник на Филозофски факултет - Скопје, 2023)
The analysis of the characteristics of the concept φρόνησις (phronesis) in Plotinus’ philosophy inevitably opens a wider discussion about the status and autonomy of ethical theory in Plotinus’ philosophy and about the relationship between contemplative and active life. On the one hand, the paradigmatic interpretations holdthat there is an otherworldly, self-centred and elitist ethics in Plotinus’ philosophy, and on the other, in the recent interpretations, the so-called “ethics of descent”, as opposed to “ethics of ascent”, the autonomy of πρᾶξις is asserted. Without examining φρόνησις with a predefined position about the status of practical ethics in Plotinus, in this article the standpoint on this issue will be formed precisely through an analysis of φρόνησις, as a key axis around which the understanding of practical reasoning and action develops. In this analysis, the connection between φρόνησις and likeness to God, understood as the ultimate goal of life, will be investigated; as well as the relationship between θεωρία and πρᾶξις, considered through the relationship between φρόνησιςand σοφία, as well as through the conception of virtue as ἕξις. The goal is to show to what extent φρόνησις, and thus ethical practice, is dependent on contemplation, that is, whether φρόνησις has an autonomous status or performs an intermediary role between the intellect and the human soul.
Keywords: Plotinus; ethics; φρόνησις; contemplation; πρᾶξις